1988. Piperacillin-tazobactam plus Ceftriaxone for Enterococcus faecalis endocarditis: A Single Center Experience. (15th December 2022) - Lee, Rachael A; Rodriguez, Martin; Stripling, Joshua; Thottacherry, Elizabeth
Abstract: Background: Enterococcus faecalis is a leading cause of Infective Endocarditis (IE). IE guidelines recommend combination of penicillin (PCN) or ampicillin (AMP) with ceftriaxone (CTX) in susceptible strains. OPAT allows for antibiotic continuation at home; however outpatient AMP is limited due to frequent dosing and instability. Piperacillin-tazobactam (PTZ) has similar but not identical activity against penicillin binding proteins (PBP) compared to AMP and PCN, suggesting that PTZ may be a substitute in OPAT. This study compares outcomes in those with E. faecalis IE discharged with either PTZ or PCN with CTX. Results of primary outcomes including death at 90 days and readmission at 90 days for those discharged on either PTZ or PCN in combination with CTX for E. faecalis endocarditis Results of non infectious complications and changes in antibiotic therapy in both groups post discharge Methods: This single center retrospective study took place from 2016 - 2020. Adults > 18 years with AMP susceptible E. faecalis IE diagnosed using Duke's criteria and blood or tissue cultures were included, with cultures confirming PCN susceptibility. Primary endpoint was failure of therapy at 90 days, defined as death due to any cause or infection relapse. Secondary outcomes were duration of antibiotics, change in regimen and non-infectious complications. Results: Overall, 34 patients were identified, 17 in each group. Average age was 60–80 years, majority having a high Charleston comorbidity index. One did not have available AMP susceptibility but was PCN susceptible. 19 were managed surgically (65% PTZ group, 47% PCN group). Average total antibiotic course was 8.2 and 7.3 weeks in PTZ and PCN groups, with average OPAT course being 4.5 and 4.4 weeks. Primary endpoint was met in 18% patients in the PTZ group and 24% in the PCN group. Of the PCN group, 1 was admitted 4 months later due to an E. faecalis device infection, outside of primary endpoint. Nearly 80% completed antibiotic therapy with 29% in the PTZ group and 35% in the PCN group readmitted for non-infectious complications, including metabolic imbalances, stroke, volume overload and gastro-intestinal bleed. Hyperkalemia was seen in the PCN group with 3 patients requiring readmission. Seizures were not reported with combined PCN and ceftriaxone. Conclusion: Similar outcomes were seen using either PTZ or PCN with CTX for treatment of enterococcal IE. Discharging patients on PCN is not always a feasible option. In these instances, PTZ could be considered as an alternative OPAT agent despite dissimilar mechanism of action compared to AMP and PCN. Disclosures: All Authors : No reported disclosures.